2020
DOI: 10.1002/tea.21627
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic beliefs and prior knowledge as predictors of the construction of different types of arguments on socioscientific issues

Abstract: This study investigates whether university students’ epistemic beliefs and prior knowledge about controversial socioscientific issues (SSIs) can predict the different types of arguments that students construct. Two hundred forty‐three university students were asked to construct different types of supportive arguments—social, ethical, economic, scientific, ecological—as well as counterarguments and rebuttals after they had read a scenario on a SSI. Participants’ epistemic beliefs and prior knowledge were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 81 publications
3
53
0
4
Order By: Relevance
“…This finding provides further support to theories which support that epistemic beliefs support reasoning (Kuhn, 1991;Iordanou 2016b) and particularly the reconciliation of contradictory exploratory accounts about complex issues (Kuhn 2019). Our finding, highlighting the role of epistemic beliefs in writing two-sided reports, is consistent with previous empirical findings (Mason and Scirica 2006;Baytelman et al 2020;Iordanou 2016b). Yet, the present study extends the literature by showing firstly that advanced epistemic beliefs are related with two-sided thinking not only in the context of neutral, usually scientific issues, but also in an emotionally-charged controversial historical issue, where individuals are more likely to exhibit biases.…”
Section: Discussionsupporting
confidence: 90%
“…This finding provides further support to theories which support that epistemic beliefs support reasoning (Kuhn, 1991;Iordanou 2016b) and particularly the reconciliation of contradictory exploratory accounts about complex issues (Kuhn 2019). Our finding, highlighting the role of epistemic beliefs in writing two-sided reports, is consistent with previous empirical findings (Mason and Scirica 2006;Baytelman et al 2020;Iordanou 2016b). Yet, the present study extends the literature by showing firstly that advanced epistemic beliefs are related with two-sided thinking not only in the context of neutral, usually scientific issues, but also in an emotionally-charged controversial historical issue, where individuals are more likely to exhibit biases.…”
Section: Discussionsupporting
confidence: 90%
“…Así, en algunos casos, como en la TD Personal y algunos de la TD Social se observa que, a mayor categoría en la expresión del modelo, mejor argumentación en todos los criterios, lo que estaría en consonancia por lo hallado por Baytelman et al (2020) respecto al conocimiento previo. De todas formas, hay que reconocer que resulta inexplicable la actuación de los y las estudiantes de la categoría más alta, M4, en la Fase 4.…”
Section: Discussionunclassified
“…particular science-related topic that is debated; Zeidler et al, 2019). However, the relationship between the particular issue and students' argumentation is still a matter under discussion (Baytelman et al, 2020;Osborne et al, 2016;Topcu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al, 2006;Pedersen & Totten, 2001), a suitable issue should preferably engage students in argumentation without requiring too much prior familiarity. In contrast to this practical demand, Baytelman et al (2020) recently suggested that familiarity about the particular issue plays an important role in constructing arguments from multiple perspectives. These perspectives are often rooted in diverse disciplines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation